2022
DOI: 10.1177/10668969221099626
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Study of Mucormycosis in Post COVID-19 Patients and Factors Affecting it in a Tertiary Care Hospital

Abstract: Introduction. COVID-19 is an infection caused by severe acute respiratory syndrome corona virus-2 (SARS-CoV-2) which may be associated with a wide range of bacterial and fungal co-infections. Mucormycosis is an opportunistic fungal infection occurring in post COVID-19 patients. Objectives. To study the role of histopathology in mucormycosis and the predisposing factors associated in development of mucormycosis in post COVID-19 patients. Materials and methods. A prospective observational study was conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…4 On the basis of its anatomic location, mucormycosis can be classified as isolated nasal, rhino-orbital or rhinoorbital cerebral, pulmonary, gastrointestinal, cutaneous, disseminated and miscellaneous. 8 In a study by Shree Laxmi et al the age of patients ranged from 21 to 80 years with a male preponderance; similar demographic details were noted in the present study. 8 The maxillary sinus was the most common affected site.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…4 On the basis of its anatomic location, mucormycosis can be classified as isolated nasal, rhino-orbital or rhinoorbital cerebral, pulmonary, gastrointestinal, cutaneous, disseminated and miscellaneous. 8 In a study by Shree Laxmi et al the age of patients ranged from 21 to 80 years with a male preponderance; similar demographic details were noted in the present study. 8 The maxillary sinus was the most common affected site.…”
Section: Discussionsupporting
confidence: 87%
“…8 In a study by Shree Laxmi et al the age of patients ranged from 21 to 80 years with a male preponderance; similar demographic details were noted in the present study. 8 The maxillary sinus was the most common affected site. The fungus gains entry into through nose and sinuses directly or blood vessels as it can penetrate vascular system.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In addition, studies including patients with invasive fungal infections in general, and not mucormycosis specifically, and studies including mucormycosis cases not associated with COVID-19 and not separately with CAM cases were excluded. Sixteen studies were excluded due to unavailable–insufficient information [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Four studies were excluded as they included patients with non-microbiologically confirmed SARS-CoV-2 infection [ 25 , 26 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%